PENGARUH PELATIHAN, KOMPETENSI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Akbar, Mohammad Abdul Aziz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to determine the influence of training, competency, and work motivation on the employees performance of PT Tangguh Karya Unggul Contraktor. The success or failure of a company in achieving success depends greatly on the ability of human resources to carry out the orders given by the company. Apart from that, human resources have an important role in realizing the goals of an organization. The population of this research is all employees of PT. Tangguh Karya Unggul Contraktor, numbering 115 people. The sampling method used is the saturated sampling method, where the number of samples is the same as the population. The data analysis method used is multiple linear regression analysis. The primary data for this research was distributed through questionnaires to 115 PT employee respondents. The resilience of Superior Works is measured using a Likert scale measuring instrument. The results of this research show that training, competence, and work motivation partially and simultaneously have a positive effect.